The Medical Scientific Liaison in an oncology busisness unit - D'Ordaz, Ana Pinto Coelho Caldeira (2018)
This monograph sets out the activities performed during the one year ‘in-job rotation’ as a Medical Scientific Liaison at Novartis Oncology medical department, within the scope of the Pharmaceutical Biomedicine Master’s degree course of the University of Aveiro. This monograph describes the first 9 months from March to December. Many were the challenges and lessons, both professional and personal. Although I already had an experience of more than 10 years working in the Pharmaceutical Industry, mostly in sales and marketing, the present enterprise has been by far the most rewarding. In the first months of this experience, the challenge was to adapt to a new function within the team. Simultaneously, to deepen my scientific knowledge concerning the solid tumours therapeutic area at this initial stage. I have acquired an essentially theoretical knowledge of some areas of the company’s organisation, at national and international level. This being a relatively new function in the Oncology business unit in Portugal, I was given the opportunity to get acquainted with it through the experience of other people inside the company. The activities were from contacts with the main doctors and investigators in Portugal, to proposals for clinical trials in new therapeutic areas, which were not yet targeted by my business unit in the past. This monograph will describe the goals of the internship and present a description of my main projects. Then the knowledge acquired through the multidisciplinary approach of the internship, followed by the description of each activity. Finally, an analysis of the difficulties and challenges I came across with, as well as the actions taken to overcome them.